In Vivo Antibacterial Activity of Dihydroanthracene Disulfonic Acid Derivative in a Case Diagnosed with Necrotizing Fasciitis - Rustemi, Florjana; Malaj, Ledjan; Bocari, Gezim; Masati, Bledi (European Scientific Journal, ESJ, 2018)
This paper focuses on reporting the in vivo antibacterial activity of dihydroanthracene disulfonic acid derivative preparation in a case diagnosed with mixed flora infection with streptococci, enterobacteria, bacterium coli, pseudomonas and anaerobic proteus that resulted in a resistant to ampicillin, piperacillin, ceftazidim, imipenem, and which is moderately sensitive to cotrimoxazole and azithromycin. This resistant infection affected a patient with history of alcohol and tobacco consumption. It later became complicated with Necrotizing Fasciitis after colon cancer surgery. This study is an in vivo study, which is aimed to measure the antibacterial activity of our new preparation against multiresistant mixed bacterial infection. In the situation of this difficult and almost hopeless case, the patient started oral and local treatment with dihydroanthracene disulfonic acid derivative. Although the fatality of the case was due to the antibiotics resistance, the patient’s treatment was attributed to the antibacterial effect of the preparation used. A significant improvement was observed in the first 24 hours after the beginning of the treatment. This happened when all parenteral antibiotics were interrupted. The improvement continued and within a couple of weeks, the wounds were clean and with visible granulation. After three months, the wounds cicatrized “per secundam”. In order to have a general conclusion regarding the in vivo study related to the treatment with dihydroanthracene disulfonic acid derivative preparation, other results are needed. The significant effect shown in the above case, demonstrates that this preparation is promising for treating life threatening resistant microorganisms infections. Further studies are needed to evaluate the full pharmacological activity of the new preparation.